A New Curve of Critical Leaf Potassium Concentration Based on the Maximum Root Dry Matter for Diagnosing Potassium Nutritional Status of Sweet Potato - Lv, Zunfu; Lu, Guoquan (Frontiers in Plant Science, 2021)
Critical leaf nutrient concentrations have often been used to diagnose the nutritional status of crops. Determining critical leaf potassium (K) concentrations for the maximum root dry matter (RDM) will provide a reliable means of linking leaf K nutrient concentrations to the yield of sweet potato. Three field experiments, using varying K application rates (0–300 kg K ha−1) and two sweet potato cultivars, were performed in the Zhejiang Province of China. A new critical leaf K curve (Kleaf) based on the maximum RDM was determined to assess K nutrition in sweet potato and described by the equation Kleaf=4.55×RDMmax-0.075. A critical root K curve (Kroot) based on the maximum RDM was also determined to assess K nutrition and described by the equation Kroot=2.36×RDMmax-0.087. The K nutrition index (KNI) was constructed to identify the situations of K-limiting and non-K-limiting treatments. The leaf KNI (KNIleaf) ranged from 0.56 to 1.17, and the root K KNI (KNIroot) ranged from 0.52 to 1.35 during the growth period of sweet potato. The results showed that the critical leaf K concentration curve can be used as an accurate leaf K status diagnostic tool at critical growth stages that connected leaf nutrient concentration and sweet potato tuber yield. This K curve will contribute to K management of sweet potato during its growth period in China.